Load Spectrum Test and Analysis of Off-road Vehicle Transmission System based on Pascar Test Specification - Zou Xihong; Liu Yanlong; Zhao Qiulin; Zhu Xiang; Yu Yong (Jixie chuandong)
Automotive transmission system load spectrum is the indispensable data foundation of automotive transmission system designing,testing and evaluating.Aiming at the off-road vehicle transmission system of an enterprise,considering the design,test,analysis other purposes,choosing the measured parameters of torque,speed,gear position,brake pedal station,clutch pedal position,lubricating oil temperature,strain,acceleration signals and etc signals,the complete synchronous test scheme for transmission system load spectrum is constructed.Rounded and accurate measurement of the transmission system load spectrum based on the Pascar test specification provide basic data and important guidance for the design,test,analysis of automotive transmission system.Wireless torque measurement problem and the synchronization problem of different channels are solved and a complete solution scheme of data collection for automotive transmission system is provided.